INTERACTIONS BETWEEN COLUMN INCLUSION AND SURROUNDING SOIL IN COMPOSITE GROUND - Gung Xin Li; Wen Feng Huang; Keizo Ugai (International Association of Lowland Technology, 2000)
The interaction between column inclusions and surrounding soil in composite ground is an important factor that the bearing capacity and settlement behaviours of the composite ground. In this paper, interaction between column inclusion (granular column or compressible pile) and surrounding soil are systematically studied by means of laboratory and field tests and tehoritical analyses. This paper presents that interaction behaviours of composite ground woith granular columns and that with compressible piles are quite different: in the former case, the interaction in mainly laterally, while in the later case, the interaction is necessary to insure enough lateral restraint for the column, especially at the upper part of the column; for the composite ground with compressible piles, a sand mat with certain thickness on the top of the pile is important to reduce the stress concentration on the columninclusion and useful to make compatible working between the column inclusion and foundation soil.